PENGARUH METODE PEMBELAJARAN STAD, PENGGUNAAN MEDIA AUDIO VISUAL DAN LINGKUNGAN SEKOLAH TERHADAP BERPIKIR TINGKAT TINGGI (HOTS) SISWA SD NEGERI SEPUHGEMBOL II - Misriah; Lilik Sri Hariani; Onik Farida Ni’matullah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the influence of the Student Teams Achievement Division (STAD) learning method, the use of audio-visual media, and the school environment on the ability of higher order thinking skills (HOTS) of students of Sepuhgembol II State Elementary School, Wonomerto District, Probolinggo Regency. The study uses a quantitative approach with ex post facto research types and causal associative designs. The research population was 165 students, while the research sample was 87 students which were determined using the stratified proportional random sampling technique. Data collection is carried out through the distribution of questionnaires and documentation. The research instrument was tested using validity and reliability tests, while data analysis was carried out through prerequisite tests and multiple linear regression analysis using SPSS 27. The results of the study showed that the STAD learning method had a positive and significant effect on students' HOTS ability. The use of audio-visual media also has a positive and significant influence on students' HOTS abilities because it is able to help students understand the material in a more concrete, interesting, and contextual way. In addition, a safe, comfortable, and conducive school environment has been proven to support the development of students' high-level thinking skills. Simultaneously, the STAD learning method, the use of audio-visual media, and the school environment have a significant effect on students' HOTS abilities. This research shows that the integration of cooperative learning methods, the use of innovative learning media, and a conducive learning environment are important factors in improving the high-level thinking skills of elementary school students. The results of the research are expected to be a reference for teachers and schools in developing more effective and innovative HOTS-based learning.